FILSAFAT PENDIDIKAN ISLAM DALAM MENJAWAB TANTANGAN PENDIDIKAN MODERN DI ERA DIGITALISASI - Racmawati Fitriyah; Wulan Sapitri; Hidayatullah; Khoiriyah (Educational Research Center, 2026)
Digital transformation in education poses significant challenges to learning processes, as rapidly advancing technologies reshape how teaching and learning take place. This study explores the relevance of Islamic educational philosophy in responding to modern educational challenges in the digital era, focusing on integrating technology into educational systems without compromising the moral and spiritual values embedded in Islamic teachings. Drawing on the epistemological and ontological foundations of Islamic education, the study argues that education aims not only to develop intellectual intelligence but also to cultivate character and virtuous conduct. The ideas of scholars such as Al-Ghazali, Ibn Khaldun, and Al-Farabi highlight the importance of synergy between knowledge and morality, which remains highly relevant to contemporary technology-influenced education. The findings suggest that technology, including artificial intelligence (AI), can be optimized to enrich learning experiences; however, it should be integrated within holistic Islamic educational principles that emphasize balance between intellectual and spiritual dimensions. The study recommends curriculum development that aligns digital content with religious values and promotes student character formation that is adaptive to changing times. Through a wise and contextual approach, Islamic education can adapt to digital developments without neglecting its moral and spiritual essence